1973
DOI: 10.1530/jrf.0.0340395
|View full text |Cite
|
Sign up to set email alerts
|

The Collection and Composition of Epididymal Plasma From the Cauda Epididymidis of the Rabbit

Abstract: A technique is described for collection of the epididymal contents from the cauda epididymidis of anaesthetized rabbits. The technique avoids undue contamination of the epididymal contents with blood or tissue fluid and overcomes the difficulty of post-mortem change. The effects of high-speed centrifugation and cold shock on the composition of epididymal plasma have also been investigated, and it has been shown that lactic dehydrogenase and glutamic\p=m-\oxaloacetic transaminase are largely intracellular const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

1975
1975
2004
2004

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…The presence of glucose in the perfusate is of interest since only trace or non-detectable amounts of reducing hexose have been found in epididymal fluid from conscious rams (White & Wales, 1961;Voglmayr et al, 1977), slaughtered bulls (Crabo, 1965;Wales, Wallace & White, 1966) or anaesthetized rabbits (Jones & Glover, 1973) (1961) and White (1973), and shown to occur in the oviducts of rabbits (Leese & Jeffries, 1977). This could be a source of energy for spermatozoa in situ, which have been shown to utilize glucose in vitro (Geer, Kelly, Pohlman & Yemm, 1975;Brooks, 1976 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of glucose in the perfusate is of interest since only trace or non-detectable amounts of reducing hexose have been found in epididymal fluid from conscious rams (White & Wales, 1961;Voglmayr et al, 1977), slaughtered bulls (Crabo, 1965;Wales, Wallace & White, 1966) or anaesthetized rabbits (Jones & Glover, 1973) (1961) and White (1973), and shown to occur in the oviducts of rabbits (Leese & Jeffries, 1977). This could be a source of energy for spermatozoa in situ, which have been shown to utilize glucose in vitro (Geer, Kelly, Pohlman & Yemm, 1975;Brooks, 1976 …”
Section: Discussionmentioning
confidence: 99%
“…Other data come from collections of fluid from the cauda epididymidis by fistulation or from the vas deferens by cannulation of conscious rams (White & Wales, 1961;Voglmayr et al, 1977) and bulls (Sexton, Amann & Flipse, 1971), or of anaesthetized rabbits (Jones & Glover, 1973), rats (Back, Shenton & Glover, 1974), guinea-pigs and hamsters (Back & Shenton, 1975). The technique of micropuncture has yielded information on the contents of proximal regions of the epididymis of rats (Levine & Marsh, 1971;Hinton, Setchell & White, 1976;Turner, Hartmann & Howards, 1977;Levine & Kelly, 1978) and hamsters (Warren, 1959) after hydrolysis in 0-1 m-H2S04 for 1 h at 80°C.…”
Section: Introductionmentioning
confidence: 99%
“…There appears to be an association between high K+ levels in the epididymal plasma and inhibited epididymal sperm movement. Potassium concentrations much higher than those in blood plasma have been reported in the caput and/or cauda fluids of the hamster (39-3 mM; Jessee & Howards, 1976), the elephant (64-8 mM; Jones, 1980), the bull (43-7 mM; Wales, Wallace & White, 1966), the rat (54 mM; Pholpramool & Chaturapanich, 1979) and the rabbit (24-8 mM in the cauda; Jones & Glover, 1973). Boender (1976) showed that boar sperm motility was depressed in media with 45-135 mM-K + and that the motility was restored by washing the same spermatozoa in a medium containing 5 mM-K +.…”
Section: Analysis Of Sperm Movement Characteristics From Video Recordmentioning
confidence: 93%
“…The significance of the increased level of GPC in rabbit plasma remains obscure. It has previously been shown (Jones & Glover, 1973a) that LDH and GOT are released from rabbit spermatozoa by prolonged high-speed centrifugation and after cold shock. In addition, there is a correlation between LDH in epididymal plasma and the occurrence of eosinophilic spermatozoa after longterm storage in the cauda epididymidis (Jones & Glover, 1973b) and after artificial cryptorchidism .…”
Section: Methodsmentioning
confidence: 99%
“…It may be assumed that the composition of epididymal plasma is the result of two interacting sources, the spermatozoa and epididymal cells (Jones & Glover, 1973a). Thus by studying changes occurring in plasma composition after various treatments, it is possible to detect whether the lining cells or the contained spermatozoa or both are adversely affected.…”
Section: Methodsmentioning
confidence: 99%